Multi-loci phylogeny reveals unexpected novelty of the Thelephora palmata complex (Thelephoraceae, Thelephorales) from China - Yu, Tai-Jie; Xue, Rou; Su, Lin-Jie; Li, Jia; Xia, Xing; Xu, Chang; Lei, Han-Chi; Zhang, Wen-Hao; Ma, Jing; Huang, Hong-Yan; Li, Xiu-Juan; Gao, Yu-Xian; et al. (Frontiers in Fungal Biology, 2025)
Thelephora palmata is a well-known species morphologically characterized by coralloid and leathery basidiomata with numerous fuscous purple to blackish-brown branches. It was once considered to exhibit a wide ecological range and distribution area. However, comprehensive phylogenetic analysis based on four loci (ITS, nrLSU, rpb2, and nrSSU) revealed that T. palmata sensu lato represents a species complex consisting of at least 12 cryptic taxa, with a biogeographic distribution pattern bounded by geographic regions: Asia, Eurasia, Europe, and North America. In this study, we proposed eight new taxa based on available specimens. Of these, seven new species and one forma from China were described here based on phylogenetic analyses, morphological examinations, and environmental niche comparisons, viz., T. apiculata, T. cornu-damae, T. densa, T. esculenta, T. fuscidula, T. sinopalmata, T. truncicola, and T. truncicola f. pallescens.